Spatiotemporal resilience assessment and comparison in China’s bay area - Han, Yu; Zhang, Yaowen; Zhang, Han; Feng, Cuicui; Hua, Tianran; Yang, Yiqun; Yun, Peng; Zeng, Jian; Peng, Li; Zeng, Jiangning; Ye, Guanqiong (Frontiers in Marine Science, 2022)
The bay area is a crucial land–sea junction zone containing essential urban clusters while receiving extremely complex internal and external disturbances that challenge more on its resilience management. However, a sound management tool based on the bay area’s resilience is widely lacking due to the difficulty of unifying resilience indicators and quantifying resilience relationships between regions. This paper tries to establish a comprehensive resilience index for coastal bays from four major resilience-related dimensions, namely, physical structure, social development, ecological environment, and hazards, and applies it into the three major developed bay areas in China. A coupling coordination degree model was used to further reveal the resilience development and its internal coordination by temporal and spatial differences. The results show that the index could clearly reveal the resilience changes from the year 2000 to 2020 of the three bays with the common key drivers of socioeconomic development. It also explains the resilience changes among three bay areas through analyzing synergistic and conflict relationships between the four sub-resilience systems.